Development of a novel electro-osmotic pump - Wang, Jianbin. (2013)
Electro-osmotic flow micropump offers the advantage of a pulse free bi-directional flow as opposed to mechanical pumps where moving parts such as actuators are need. Also, because of the concept of electro-osmosis which requires just an electric field to cause fluid motion would enable the pump design to be simple and easy for fabrication.